ดุษฎีนิพนธ์การประพันธ์เพลง: เทพยดินแดน "เชียงราย"สำหรับวงแจ๊สอองซอมเบิลร่วมสมัย - ดิเรก เกตุพระจันทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Doctoral Music Composition: Legend of the Fairy Kingdom "Chiangrai" for Contemporary Jazz Ensemble, is a creative program music to explore the cultural and literary sound of the legendary city "Chiangrai". A set of six characterizing features were expressed the historical legacies taken place in the ancient city from past to present via the gimmick of contemporary Jazz technique and element of regional ethnic music as combinations. The program characters of the music consists of 1) Yonok Nakorn (The fallen ancient city), 2) Lamkha Doi Tung (Privilege of the mountain palace), 3) Phra Kaew Morakot (Journey of the Emerald Buddha), 4) Tam Luang Nang Non (The Giant Cave of the Sleeping Goddess) 5) Wat Rong Khun (The Symbolic Temple), 6) Kwaung Song Maha Bhaya (The Chiangrai United Football Club). The integrated compositions are required professional and skillful musicians in order to transmit the traditional northern sound and Jazz harmonic progression into the highly imaginative improvisations which is the spectacle highlight of the entire composition. The 33 minutes duration music has played an important role in enhancing cultural unity and the pride of historical legacy.